(untitled) (The Pakistan Development Review, 1980)
This paper deals with the adaptation of traditional Western textbook economic theory to the problems of developing countries. It treats wages, rents and interest together with Keynesian and classical economy-wide models from this standpoint. The value of labour’s marginal product will vary with the wage, rents with the land tenure system and interest rates with the size of and security on a loan. Inflationary Keynesian-inspired growth is likely to be unacceptable. Advance must therefore occur in a supply-originated classical manner.